2020
DOI: 10.3390/cancers12020270
|View full text |Cite
|
Sign up to set email alerts
|

Multistate Markov Model to Predict the Prognosis of High-Risk Human Papillomavirus-Related Cervical Lesions

Abstract: Cervical intraepithelial neoplasia (CIN) has a natural history of bidirectional transition between different states. Therefore, conventional statistical models assuming a unidirectional disease progression may oversimplify CIN fate. We applied a continuous-time multistate Markov model to predict this CIN fate by addressing the probability of transitions between multiple states according to the genotypes of high-risk human papillomavirus (HPV). This retrospective cohort comprised 6022 observations in 737 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Moreover, the progression and regression rates were similar between patients with other hrHPVs and those with no hrHPVs. These results are consistent with those seen in the literature and corroborate the finding that patients with HPV 16 are more likely to develop more severe lesions than those with HPV 52, HPV 58, other hrHPVs, or no hrHPVs 6 . By applying the hidden Markov model to accommodate the diagnostic misclassification, our study confirmed the robustness of the current literature on CIN characteristics according to HPV genotype.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the progression and regression rates were similar between patients with other hrHPVs and those with no hrHPVs. These results are consistent with those seen in the literature and corroborate the finding that patients with HPV 16 are more likely to develop more severe lesions than those with HPV 52, HPV 58, other hrHPVs, or no hrHPVs 6 . By applying the hidden Markov model to accommodate the diagnostic misclassification, our study confirmed the robustness of the current literature on CIN characteristics according to HPV genotype.…”
Section: Discussionsupporting
confidence: 92%
“… 111 Persistent high-risk human papillomavirus (HPV) infection is considered a leading cause of cervical cancer, and the HPV oncogenes E6 and E7 play an essential role in this process. 112 , 113 However, a few patients with cervical cancer do not show HPV infection; thus, preventing high-grade cervical intraepithelial neoplasia (CIN) from developing into invasive cervical cancer through early screening is crucial. 114 …”
Section: The Role Of Exosomes In Cervical Cancermentioning
confidence: 99%
“…HPV31/33 infections have also been reported to promote cervical carcinogenesis worldwide [7][8][9][10]. HPV52 and 58 are the genotypes with oncogenic potential and high prevalence in Asia regions [10,11]. The 5-year risk for cervical intraepithelial neoplasia grade 2 and above (CIN2+) was much higher (45.3%) in women with mild abnormal cervical cytology than that (12.9%) in women with normal cervical cytology [12], suggesting that women with normal pathology screened from abnormal cervical cytology were a special population with higher progression risk than women with normal cytology.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…A PCR-based flow-through hybridization and gene chip system were used for HPV hybridization and color rendering. Purple 11,42,43,44,and CP8304). HR-HPV infection meant that at least one HR-HPV genotype was positive.…”
Section: Hpv Genotyping Detectionmentioning
confidence: 99%